(untitled) (Al-Qamar, 2022)
News headlines are designed to present a story in a meaningful way to grab the attention of readers where editor use emotionally charged language as a tool to make the title of story more memorable and responsive. In religious domain, spiritual orientation and attribution to the holiness is often viewed to function influential communication. This research aims to analyze Sufi orientation investigating headlines published in leading national language dailies. We applied qualitative content analysis method in this study to analyze the headlines and used purposive sampling technique to collect the data; for a comprehensive overview, this paper calls attention to the news stories printed on the occasions of death anniversaries of prolific Sufi saints of the region, Punjab, Pakistan, in four leading newspapers, Nawa-i-Waqt, Jang, Express and Khabrain, to contribute to the contemporary studies of religion and press. The study found that editors engaged and encourage readers to want to find out more presenting Sufi as a great preacher and a source of love, peace and divine blessing. This paper argues that in Sufi headlines divine faith and religious achievements of the saints can be discerned to induce a sense of reverence of the religious mentors and to appeal reader’s cognitive connections of their faith.